Time to Develop Phlebitis and Its Predictors Among Patients with Peripheral Intravenous Cannula at Public Hospitals of Bahir Dar City, Amhara, Ethiopia, 2022: A Prospective Observational Study - Lidetu Bayeh T; Yirga Birhie A; Mesfin Alene E (Dove Medical Press, 2023)
Tadios Lidetu Bayeh,1 Alemshet Yirga Birhie,1 Elisabet Mesfin Alene2 1Department of Adult Health Nursing, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Nursing, Felege Hiwot Referral Hospital, Bahir Dar, EthiopiaCorrespondence: Tadios Lidetu Bayeh, P.O. Box 1072 Bahir Dar, Bahir Dar, Ethiopia, Tel +251955185671, Email tadioslidetu@gmail.comBackground: Phlebitis is an inflammation of vein and the common complication of peripheral intravenous cannula. Phlebitis leads patient to sepsis, pulmonary embolism and other serious complications that increase patient morbidity and mortality. Phlebitis-related literature is scarce in Ethiopia. Therefore, the incidence and predictors of phlebitis were the focus of this study.Methods and Materials: An institution-based prospective observational study was carried out at public hospitals of Bahir Dar city. Four hundred sixty-two patients with peripheral intravenous cannulas who were admitted to the medical ward were selected using a systematic random sampling technique. Jackson's Visual Infusion Phlebitis Scoring system was used to determine the presence of phlebitis. We used Cox proportional hazards regression model, to identify significant predictors of phlebitis.Results: In this study, 462 patients included, and 171 (37.01%) of them developed phlebitis. The median survival time of phlebitis was six days. Patients whose age group > 60 years had low probability to develop phlebitis (AHR = 0.49, 95% CI 0.29- 0.82), whereas chronic-diseases (AHR = 1.50, 95% CI 1.09- 2.07), drugs and blood administer in one vein (AHR = 2.03, 95% CI 1.44- 2.86), inappropriate cannula dressing (AHR = 1.81, 95% CI 1.31- 2.51), large cannula size (AHR = 1.52, 95% CI 1.08- 2.15) and longer cannula dwelling time (AHR = 7.39, 95% CI 4.12- 13.32) had high probability to develop phlebitis.Conclusion: The post-peripheral intravenous cannula phlebitis that frequently affects hospitalized cannulated patients requires particular attention and follow-up for cannulated patients with known risk factors.Keywords: time, incidence, predictors, phlebitis, cannula, patients